Identity Fraud In Polygamy, A Review Of Court Decisions - Hidayati, Taufika; Erma, Zetria (IHSA Institute, 2024)
Marriage is a form of worship because it has a noble purpose to maintain human survival as stated in the Qur'an. It is hoped that a marriage will be carried out forever and without anything being hidden. In Islam, a husband is allowed to have more than one wife (polygamy) as long as he can act fairly and comply with applicable regulations. When you want to remarry, one of the conditions is the wife's consent and permission from the Religious Court. The husband committed the falsification of his identity when he was about to remarry. Through analytical descriptive research, this article aims to understand the terms and conditions of polygamous marriages and for husbands to understand the impact of the law on falsifying identities in marriage. The presence of identity falsification is one of the judge's considerations in handing down a decision to annul a marriage